Hubungan Pengetahuan, Sikap, dan Perilaku Ibu dalam Pemenuhan Kebutuhan Dasar Anak terhadap Status Gizi Anak Usia Dini Selama Pandemi COVID-19 - Elok Permatasari; Devi Arine Kusumawardani (Universitas Muhammadiyah Jember, 2022)
Background and Aim: Parents have an essential role in supervising and nurturing their children during a pandemic. Whatever the condition, the basic needs of children, namely honing, loving, and caring, must still be given to support the growth and development of children. This study aims to analyze the relationship between knowledge, attitudes, and behavior of mothers in fulfilling basic needs on the nutritional status of early childhood. Methods: The design of this study was a cross-sectional study conducted on parents of early childhood at Al Amien Kindergarten Jember a respondent. The population in this study was all parents totaling 282 parents. The sample calculation used the formula of Snedecor and Cochran for the cross-sectional study and obtained a sample size of 72 parents. Data was collected using a questionnaire with a google form. Results: Most mothers have excellent knowledge, attitudes, and behaviors to fulfill the basic needs of early childhood during the pandemic. The nutritional status of most young children, based on BMI, is also in good condition. However, there is no significant relationship between knowledge (p-value=0,295), attitude (p-value=0,824), and behavior (p-value=0,522) in fulfillment children's basic needs with early childhood nutritional status. Conclusions: Fulfillment of the basic requirements of early childhood must still be given to children regardless of their condition. Fulfilling basic needs has a long-term effect on children's growth and development in the future.